The End and the Beginning : The Revolutions of 1989 and the Resurgence of History - Iacob, Bogdan; Tismaneanu, Vladimir (Book collections on Project MUSE., 2012)
A fresh interpretation of the contexts, meanings, and consequences of the revolutions of 1989, coupled with state of the art reassessment of the significance and consequences of the events associated with the demise of communist regimes. The book provides an analysis that takes into account the complexities of the Soviet bloc, the events' impact upon Europe, and their re-interpretation within a larger global context. Departs from static ways of analysis (events and their significance) bringing forth approaches that deal with both pre-1989 developments and the 1989 context itself, while extensively discussing the ways of resituating 1989 in the larger context of the 20th century and of its lessons for the 21st. Emphasizes the possibility for re-thinking and re-visiting the filters and means that scholars use to interpret such turning point. The editors perceive the present project as a challenge to existing readings on the complex set of issues and topics presupposed by a re-evaluation of 1989 as a symbol of the change and transition from authoritarianism to democracy.